Stemphylium lycopersici isolates virulence depends on the synthesis of phytotoxic metabolites, which is modified by the environment - Medina, Rocío (2018)
Stemphylium lycopersici is one of the causative agents of Tomato grey leaf spot. We found that the genome of S. lycopersici CIDEFI-216 contains several putative secondary metabolite (SM) gene clusters, which have been associated to different biological roles. We hypothesized that isolates of S. lycopersici that differ in their virulence and ability to sporulate synthesize a different array of SMs. Three isolates of the fungus that differ in virulence and sporulation capacity were grown on V8 and PDA plates at 25°C for 14 days. SMs were obtained from lyophilized cultures through sonication and ultrafiltration. Spectroscopic UV–Vis absorption spectra and fluorescence–excitation-emission matrices as well as phytotoxicity of the fungal extracts were evaluated. The absorbance spectrum showed that all the extracts had a 450-nm peak and that isolate CIDEFI-216 grown on V8 medium contained the most complete array of peaks, metabolites. Fluorescence intensity and emission was a function of the fungal isolate and the culture medium. Extracts from CIDEFI-216 presented the highest fluorescence emission spectra, and all of them provoked lesions on tomato leaflets (p<0.05), which were greater provided the fungus was grown in V8 medium. Here we demonstrate that SMs are key variable factors in the necrotrophic ability of S. lycopersici isolates, which can be drastically modified by the environment where the fungus grows.